2015
DOI: 10.1007/s00396-015-3606-8
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a thermo-sensitive poly(N-acetyl-L-glutamic acid-co-lysine ester) with excellent biocompatibility

Abstract: Non-cytotoxicity or good biocompatibility is an essential requisite for the thermo-sensitive polymeric materials used in the biomedical fields. In this study, a new poly(Nacetyl-L-glutamic acid-co-lysine ester) (PGAL) with excellent thermo-sensitivity and biocompatibility is synthesized from natural lysine and glutamic acid. The chemical structures of the monomers and polymers are determined by 1 H NMR, FTIR spectrum, and GPC. PGAL shows a reversible lower critical solution temperature (LCST) of 17.3-31.7°C, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The structural prerequisites for thermosensitive polymers are the existence of hydrophilic and hydrophobic groups bonded onto the macromolecular chains . A relative balance between the hydrophilic interactions and hydrophobic interactions from the polymer is also required in solvents such as water . For the three homopolymers, poly(acetyl amino acrylate) and poly(propionyl amino acrylate) are completely soluble in water due to their high hydrophilicity and poly(benzoyl amino acrylate) is insoluble in water because of its higher number of hydrophobic groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The structural prerequisites for thermosensitive polymers are the existence of hydrophilic and hydrophobic groups bonded onto the macromolecular chains . A relative balance between the hydrophilic interactions and hydrophobic interactions from the polymer is also required in solvents such as water . For the three homopolymers, poly(acetyl amino acrylate) and poly(propionyl amino acrylate) are completely soluble in water due to their high hydrophilicity and poly(benzoyl amino acrylate) is insoluble in water because of its higher number of hydrophobic groups.…”
Section: Resultsmentioning
confidence: 99%
“…Our group has extensive experience in researching the molecular design and preparation of thermosensitive polymers and has synthesized a variety of new thermosensitive polymers. [19,20,[24][25][26] It was found that qualitative descriptions of these structural requirements can be transformed to quantitative expressions regarding the synthesis of thermosensitive polymers. That is, every practical hydrophilic group on the polymer chain that is described has a certain number of hydrophobic moieties.…”
Section: Doi: 101002/macp201900349mentioning
confidence: 99%
See 3 more Smart Citations